2016
DOI: 10.1007/s10903-016-0354-x
|View full text |Cite|
|
Sign up to set email alerts
|

Coming of Age on the Margins: Mental Health and Wellbeing Among Latino Immigrant Young Adults Eligible for Deferred Action for Childhood Arrivals (DACA)

Abstract: Undocumented immigrant young adults growing up in the United States face significant challenges. For those qualified, the Deferred Action for Childhood Arrivals (DACA) program's protections may alleviate stressors, with implications for their mental health and wellbeing (MHWB). We conducted nine focus groups with 61 DACA-eligible Latinos (ages 18-31) in California to investigate their health needs. Participants reported MHWB as their greatest health concern and viewed DACA as beneficial through increasing acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 30 publications
1
78
1
1
Order By: Relevance
“…This general mistrust within the API community, even within their own ethnic groups, decreased bonding social capital and led to feelings of social isolation among young adult APIs. This is in stark contrast to studies among undocumented Latino young adults populations that found strong peer support (Siemons et al, 2016) and strong social solidarity among broader Latino immigrant populations (Hoyt, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This general mistrust within the API community, even within their own ethnic groups, decreased bonding social capital and led to feelings of social isolation among young adult APIs. This is in stark contrast to studies among undocumented Latino young adults populations that found strong peer support (Siemons et al, 2016) and strong social solidarity among broader Latino immigrant populations (Hoyt, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Community-based organizations and legal service providers in API and Latino immigrant communities have attributed this disparity to API's increased sense of shame and stigma, loss of status within their communities due to their documentation status, and mistrust in governments (Rusin, 2015). Undocumented young adult Latinos, on the other hand, have been found to have high community social support (Siemons et al, 2016). Undocumented immigrants, and APIs in particular, live in the shadows of society, and there is a need to better understand how social ties to families and communities impact health access and status.…”
Section: Linking Social and Community Contexts To Health Among Undocumentioning
confidence: 99%
“…Because transitory youth now feel more vulnerable than when they were undocumented, they reported curtailing their interaction with the health care system and worsening mental health status. Previous research on social capital showed that despite divisions among the Latino communities 46 , intra-ethnic support among undocumented Latino communities was relatively strong 47 . Our results further seem to indicate that their transitory legal status and perceptions of social stigma as a result are undermining their feelings of community cohesion, causing them to experience feelings of alienation even from their peers.…”
Section: Discussionmentioning
confidence: 96%
“…Health care access, use of services, and experiences among undocumented Mexicans and other Latinos. Archives of Internal Medicine, 167 (21), 2354-2360. 16 North, Anna.…”
Section: Undocumented Immigrant Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation